Pemberdayaan Masyarakat melalui Badan Kontak Majelis Taklim (BKMT) Kecamatan Tayan Hilir Kabupaten Sanggau pada Kegiatan Sosialisasi dan Pendampingan Sertifikasi Halal - Hermansyah, Hermansyah; Suhardiman, Suhardiman; Suhaimi, Suhaimi; Noviansyah, Noviansyah; Syahrun, Muhammad; Mahwa, Ilal (Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2025)
This community service activity was motivated by the challenges faced by Micro, Small, and Medium Enterprises (MSMEs) in fulfilling their halal certification obligations under the Halal Product Assurance (JPH) Law. Literacy and technical barriers in the certification process often hinder the potential for economic independence of MSMEs. Therefore, the Majelis Taklim Contact Body (BKMT) was identified as a strategic partner with a strong community base to reach home-based MSMEs and raise halal awareness at the family level. This community service program aims to increase the awareness and economic capacity of BKMT members and their mentored MSMEs. Specifically, this activity includes increasing understanding of JPH, technical training on developing a Halal Assurance System (SJH), and intensive mentoring to facilitate the acquisition of Halal Certification. The community service implementation method uses a participatory and educational-applicative approach, divided into four stages: preparation (needs identification), outreach (halal education and regulations), technical mentoring (SJH implementation and SiHalal registration), and evaluation and sustainability.The main outcomes of this program are increased literacy and public awareness of the importance of halal certification, the acquisition of Halal Certificates for MSME members of the BKMT, the provision of materials for socialization and assistance with halal certification, and the establishment of a Halal Task Force within the BKMT as a model for sustainability. Thus, this program is expected to achieve Sharia-based economic independence for the community by increasing the competitiveness of MSMEs and ensuring the right and awareness of halal product consumption for Muslim families.